Long-Term NMDAR Antagonism Correlates Weight Loss With Less Eating - Deng, Shi-Ning; Yan, Yu-Hua; Zhu, Tai-Lin; Ma, Bing-Ke; Fan, Hui-Ran; Liu, Yan-Mei; Li, Wei-Guang; Li, Fei (Frontiers in Psychiatry, 2019)
Memantine hydrochloride is an uncompetitive N-methyl-D-aspartate (NMDA) antagonist for treatment of moderate-to-severe Alzheimer's disease. Several studies have shown that memantine can significantly correct the binge-like eating behavior in human and animal models. People with overeating behavior are more likely to be obese. Therefore, we suppose that memantine would be a good candidate for the treatment of obesity. In this study, memantine was shown to increase weight loss in obese mice induced by high fat diet. Memantine was shown to decrease food intake without inducing abdominal discomfort and anxiety, suggesting that this compound would be a good candidate drug for obesity control.